The Canadian Western Arctic: A Century of Change - Usher, Peter (Anthropologica, 2022)
Demographic, economic and social changes among the Eskimo population of the Western Arctic during the four major phases of white-Eskimo contact are examined. Journals from the exploration era provide a baseline from which change can be measured. The whaling and fur trade eras caused profound demographic changes and served to orient the Eskimos to a commercial economy. The modern era has forced a shift off the land to an urban wage economy, and this has had a more profound impact on the Eskimo way of life than the changes which occurred in earlier eras.